Using Ethical Standards Accounting in the Assessment of Directors - Voss , Grażyna (Studia Oeconomica Posnaniensia, 2016)
A Code of Professional Ethics in Accounting is a set of ethical standards, compliance with which is an indispensable element of modern accounting. Their scope and practical application leaves no doubt as to why a company should take all possible steps to allow for their proper and widespread use. The standards should not only be enforced by accountants, but also by the heads of business units. Rating the practical application of ethical standards in their opinion raises serious concerns and should strengthen the role of professional ethics by taking various measures to promote, educational or simplify safeguards and certifying compliance with ethical standards by individuals. The introduction of such solutions requires changes in the regulatory environment and way of thinking of all operators in the market.